Fair value accounting is the wrong scapegoat for this crisis - Nicolas Véron (Bruegel, 2008)
The ongoing financial crisis has revived the longstanding debate about fair value accounting. This policy contribution by Nicolas Véron argues that in times of market disruption, no accounting standards could lead to consensual outcomes, and that fair value remains better than proposed alternatives. Rather than reducing its scope, policymakers should focus on capital requirements standards (Basel II), where the negative effects of 'pro-cyclicality' are concentrated.
Keywords: 330